Biological characterization and inhibitors action of Phospholipase A2 from Lachesis muta venom - Inga, Rosalina (2010)
In the present study, phospholipase A2 (PLA2) from Lachesis muta (Linnaeus, 1766), is isolated, purified and characterized biochemically and biologically. Purification was performed by liquid chromatography (LC) using CM-Sephadex C-50 and Sephadex G-50, homogenized enzyme had a molecular weight of 18749 Da. Trials with egg yolk phospholipids, and commercial lecithin showed that EDTA, PMSF, glutathione and cysteine inhibited the activity with values greater than 50%. The PLA2 had a significant anticoagulant effect, showing a delay of 2'30" on the coagulation time with 9.6 µg of the enzyme. The indirect impact on human erythrocyte hemolysis gave an equivalent of 4.35 µg as HD50. Mean edematic dose and minimum myotoxic dose were 91.5 mg and 125.89 mg / mL respectively, these values were below enzymes phospholipase A2 from others poisons. There was no hemorrhagic activity. Immunodiffusion tests and immunoelectrophoresis revealed that the PLA2 of L. muta was immunogenic reactivity against lachesic monovalent antivenom (INS-Peru). However, the neutralization by the antivenom was partial.